Critical Analysis of Cross-Cutting Themes in Healthcare Systems and Practices - Alharby, Bader Saad F; Alsuwaylimi, Bayan khaled; Alzehairi, Faisal Mohammed; Al zuair, Saad Mohammed Saad; Safar, Fahad Adnan; Alenezi, Bashayer Sameer; Alenazi, Tahani Awdah; Alanazi, Manal Halal; Alhamad, Hesham Mohammed; Alsaeed, Meteab Mohammed; Alonyzi, Azeza Mohmmad (Journal of Ecohumanism, 2024)
Every healthcare system in the world experiences a variety of challenges as well as opportunities as they attempt to deliver healthcare services that are accessible, efficient, and, most importantly, equitable. This review presents general areas of interest in health systems and implementation sciences while appreciating trends, barriers, variations, and innovations influencing the systems and practices in producing improved patients’ health status. It includes topics like access/travel to care, service quality, payment/reimbursement processes, human resources in the healthcare sector, and technology in/impact of healthcare. The recommendations in this paper are targeted at enhancing global healthcare practices through shared and integrated practices involving technology and considering health equity.